Philanthropy of Pesantren Towards Socio-Economic Welfare (Study At Markaz Bayt Al-Musaadah Social Institution, Mambaus Sholihin Gresik Islamic Boarding School) - Havy, M. Havy Sa’dullah; Nurhayati; Arifin, Sirajul (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
Cases of misuse of social funds have slowed down welfare programs for the poor and dhuafa’. The establishment of Markaz Bayt Al-Musa’adah under Pesantren Mambaus Sholihin provides a breath of fresh air, with pesantren now required not only to produce a generation that understands religion, but also as a pillar of Islamic sharia economics. This research uses a qualitative method with a case study approach to explore the economic empowerment and management of philanthropic funds by Markaz Bayt Al-Musa’adah of Pesantren Mambaus Sholihin Gresik. This method involves in-depth data collection and various sources of information as well as participation in the field. The results show that Markaz Bayt Al-Musa’adah has implemented community economic empowerment through skills training programs and assistance to underprivileged students. The management of social funds is carried out transparently and accountably based on the principles of Islamic philanthropy, with managers working without taking profits, solely for the sake of Allah and the intention of khidmah to the caregiver.